The Importance of Applying Governance Principles in Zakat & Waqf Funds Management": The Case of Algerian Zakat & Waqf Funds - Siham , AISSAOUI; Fattoum, HOUHOU (Milev Journal of Research and Studies, 2020)
As a result of increased administrative and financial corruption and the lack of management integrity and transparency in their dealings, increased attention to corporate governance, which is a mechanism to reduce the negative practices, and institutions working to develop and improve their performance, The Institutions Islamic finance, like other institutions need for This mechanism, in order to bring many of the regulatory and administrative reforms, and activating the role. The Zakat and Waqf Fund One of the Islamic financial mechanisms And the application of the principles governance in management helps to balance Between economic and social objectives, leading to efficient use of resources and the establishment of justice and the values of transparency and accountability and ensures the integrity of the transactions and enhance the confidence of people